Effectiveness of an Educational Program on Primary School Teachers’ Knowledge about Attention -Deficit/Hyperactivity Disorders - Hassam M. Al-Amarei1 , Saja H. Mohamed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The child is one of the most important assets of the nation, the future of mankind, the source of its true power, the promotion and enhancement of the child’s life and welfare is also anchored on the moral supervision and support given by his parents or guardians in order for a child to succeed, parents exert a lot of influence on their child’s cognitive development in the early years, the investigator made an insight into the aim of the study as follows: To determine the effectiveness of the teaching program on teachers knowledge. The study was conducted on at governmental primary schools in Al-Najaf City/ Iraq. A total of the (10) governmental primary schools selected randomly from total (253) governmental primary schools in Al-Najaf City. A purposive (non- probability) sample of (70) primary school teachers’ were selected from the candidate schools were included in the present study. During the period of 1st September 2018 to 20th February 2020. The data was collected by questionnaire which consisted of two main parts, first part consists socio demographic sheet. Second part is about knowledge which consist of (31) items scale of teachers’ knowledge about children with ADHD . Findings revealed confirmed that the teachers who not attended for program about ADHD have poor level of knowledge pupils with attention -deficit/hyperactivity disorder among elementary school teachers. While the teachers who attended for program about ADHD have improve and increase knowledge about ADHD in phase two, and three. Thus, it is recommended for responsible parties to notes the need for greater efforts to teachers should trained to recognize students with behaviors problems / disorders in their classes to provide them with proper and timely education as well as necessary referral for their assessment.